Collaborative case-based learning process in research ethics - Anu Tammeleht; María Jesús Rodríguez-Triana; Kairi Koort; Erika Löfström (International Journal for Educational Integrity, 2019)
Abstract The increasing concern about ethics and integrity in research communities has brought attention to how students and junior academics can be trained on this regard. Moreover, it is known that ethical behaviour and integrity not only involve individual but also group norms and considerations. Thus, through action research and participant observation, this research investigates the learning processes through which 64 students collaboratively develop research ethics and integrity competencies. The aim was to understand how bachelor, master and PhD students approach ethical dilemma cases through a collaborative process. The data consisted of recorded group work on ethics cases, student group reports, and post-training questionnaires. Later, the analyses considered groups as the unit of analysis. These data were analysed through content analysis utilizing the SOLO taxonomy to identify levels of understanding and assess evolvement of ethical sensitivity during a case-based training session. The results show that all groups reached the level of understanding where the groups demonstrated that concepts had been understood appropriately, but occasionally struggled to make connections between them. Students perceived working collaboratively as beneficial. The results help teachers of research ethics and integrity to make pedagogically justified choices in their teaching. Drawing on the results of this study, we propose a tool for the formative assessment of student learning of research ethics and integrity.